Reduction of bacteria in storage system of sewage effluents - Abduh Algheethi, Adel Ali Saeed; Mohamed, R. M.; Efaq, A. N.; Norli, I.; Adib, M. R.; Amir, H. M. K. (Springer, 2017)
The present work is aimed to investigate the linear regression model of total coliform (TC), faecal coliform (FC) and enterococci (ENT) responses in the storage system of sewage effluents at different temperatures (room temperature 25 ± 2 °C, 55 and 65 °C). Five litres (v/v) of sewage effluent samples was stored at room temperature (25 ± 2 °C) for 1, 2, 3 and 4 weeks. In order to investigate the response of bacteria to the storage system at thermal conditions, the sewage samples were stored at the temperatures of 55 and 65 °C in a water bath shaker for 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110 and 120 min, respectively. The results indicated that the storage system at room temperature significantly (p < 0.01) effected the reduction of TC (33%), FC (36.6%) and ENT (47.8%). Moreover, sewage effluent met WHO guidelines after two weeks of storage period at room temperature. The storage system at 55 and 65 °C had more significant influence (p < 0.01) on TC, FC and ENT. The reductions for TC, FC and ENT were 49.6 versus 64, 47.7 versus 83.2% and 47.4 versus 57.3%, respectively. ENT (Gram-positive bacteria) exhibited more resistance to the storage system at 65 °C than TC and FC (both are Gram-negative bacteria). This might be due to the differences in the cell wall structure. It can be concluded that the storage system of sewage effluents has a significant potential for the reduction of indicator bacteria.